Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3346/jkms.2013.28.9.1382
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Deep Vein Thrombosis after Spinal Cord Injury in Korean Patients at Acute Rehabilitation Unit

Abstract: Deep vein thrombosis (DVT) and subsequent pulmonary embolism (PE) remain significant causes of morbidity, mortality in patients with spinal cord injury (SCI). Since incidence of DVT after SCI in Korean population has not been much studied, we retrospectively analyzed the medical records of 185 SCI patients admitted for acute rehabilitation unit to investigate the incidence of DVT. Color Doppler ultrasonography was performed to screen for the occurrence of DVT at the time of initial presentation to acute rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 23 publications
4
30
1
1
Order By: Relevance
“…21,22 According to various authors, the percentage of detected distal DVT ranges from 5 to 76.5%. 23,24 DVT pharmacological prophylaxis with LMWH decreases its rate of what has been reported through multiple studies. 5,14,25,26 Most of the authors recommend the aforementioned level of prophylaxis until the end of the 2nd 1,25 or 3rd month post-injury.…”
Section: 3710mentioning
confidence: 99%
“…21,22 According to various authors, the percentage of detected distal DVT ranges from 5 to 76.5%. 23,24 DVT pharmacological prophylaxis with LMWH decreases its rate of what has been reported through multiple studies. 5,14,25,26 Most of the authors recommend the aforementioned level of prophylaxis until the end of the 2nd 1,25 or 3rd month post-injury.…”
Section: 3710mentioning
confidence: 99%
“…There are a number of potential reasons for this, including the recovery of muscle stretch reflexes and tone following the acute period of spinal shock (DeVivo, 1999;Do, 2013). Data from the federally designated Spinal Cord Injury Model Systems demonstrate that the annual risk for DVT among chronic SCI patients (1.1% one to six years after injury) is much lower than that for acute SCI patients, and the risk for PE is even lower (0.3%) (Ragnarsson, 1995).…”
Section: Venous Thromboembolism In Spinal Cord Injury: Risks and Riskmentioning
confidence: 99%
“…Similarly, among acute SCI patients managed at the Mayo Clinic from 1976 to 1995, the use of DVT screening was the strongest predictor of a VTE diagnosis, with a risk ratio of 2.8-fold compared with patients not screened (Winemiller, 1999). Three retrospective studies reported a high rate of asymptomatic DVT when routine DUS was performed in SCI patients on transfer to a rehabilitation center (Powell, 1999;Kadyan, 2003;Do, 2013). DVT was detected in 12% of 189 patients, 9% of 92 patients, and 28% of 185 patients on admission to SCI rehabilitation (Powell, 1999;Kadyan, 2003;Do, 2013).…”
Section: We Suggest That Sci Patients Not Be Routinely Screened With mentioning
confidence: 99%
See 2 more Smart Citations